Pathogenicity of fungal pathogens isolated from infected soursop in Bukit Kurau, Perak / Nurul Syafika Muslimin ... [et al.] - Muslimin, Nurul Syafika; Mohd Yusof, Farida Zuraina; Abdul Khalil, Khalilah; Boll Kassim, Qursyna (Faculty of Applied Sciences, 2023)
Plant rot disease is considered as one of the major constraints in soursop fruit production. Various fungal causal agents caused diverse rot diseases of soursop trees in Peninsular Malaysia but the extensive study in the determination of the species of the pathogen is yet widely demonstrated. Thus, this study was aimed to identify the fungal pathogen associated with the infected soursop trees and its pathogenicity level. Eight different fungal species were isolated from the infected soursop trees on a private farm in Bukit Kurau, Perak. The fungal species identified as Pseudopestalotiopsis theae, Penicillium simplicissimum, Purpureocillium lilacinum, Penicillium javanicum, Fusarium oxysporum, Aspergillus sydowii, Diaporthe phaseolorum and Trichoderma asperellum. Among them, F. oxysporum demonstrated the highest pathogenicity activity towards soursop sapling. The symptoms include wilting, black spots, and yellowish- green leaves. Meanwhile, the rest of the species exhibit mild pathogenicity activity whilst P. theae does not affect the soursop sapling. This study presents useful insight on the pathogens of soursop rot disease and its pathogenicity activity.